Crianças e notícias: Uma abordagem teórica e enquadramento das principais investigações desenvolvidas entre 2000 e 2011 - Silveira, Patrícia (2012)
Recent studies show that media are part of children’s everyday life from an early age (KOTILAINEN, 2011). However, there is little research about problems of everyday life, such as the relationship between children and current affairs. And if we consider that media are the main drivers of information and constructors of a symbolic environment, there is a need for research about what kind of representations children create around this media environment, and also to understand how they create references to stand in the world. This paper is part of a doctoral thesis, in development, and consists on a survey and analysis of the studies carried out in the last decade, about new generations and media, specially the relationship between children and the news. For this, it was made a documentary research, between 2000 and 2011, on the database Communication Abstracts. Apart from a perspective of what has been investigated in the last years, sensing the main aspects incorporated in these studies and possible gaps, it is essential to understand the place and importance of media in children`s lives, as well as the connection they establish with the news. The results show that investigations tend to emphasize the effects of certain contents (violence, crime) on children, rather than leave the meanings constructed by these social actors, in order to emphasize the recognition of participation rights, legitimated by the Convention on the Rights of the Child (1989).